Definition of C282Y mutation in a hereditary hemochromatosis family from Turkey - Oya YÖNAL; Özden HATIRNAZ; Filiz AKYÜZ; Gupse KÖROĞLU; Uğur ÖZBEK; Kıvanç ÇEFLE; Zeynel MUNGAN (Turkish Journal of Gastroenterology, 2019)
-